(untitled) (Scientific journal of the Fergana State University, 2023)
By neutron activation analysis method the component composition and quantitative content of 39 macro - and microelements in aboveground parts of medicinal plants of the Ferghana valley has been defined. The qualitative composition of the elements of the overground part of the difference is observed only in quantitative content of individual components. The investigated plant species is promising sources of macro - and microelements.